Resin composition and electronic component device
Patent Information
- Application Number
- JP2024073131
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2016-12-27
- Filing Date
- 2024-04-26
- Publication Date
- 2025-04-07
AI Technical Summary
The increasing heat generation in miniaturized and densified electronic component devices necessitates resin compositions with high thermal conductivity and excellent fluidity, but the addition of inorganic fillers often leads to increased viscosity and reduced fluidity, causing incomplete filling.
A resin composition comprising inorganic particles with a specific particle diameter range and surface area, along with a balanced proportion and specific gravity ratio, to maintain fluidity while enhancing thermal conductivity.
The resin composition achieves improved fluidity and thermal conductivity, ensuring effective sealing and filling of electronic components.
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition and an electronic component device. [Background technology]
[0002] 2. Description of the Related Art Conventionally, packages (electronic component devices) in which elements such as transistors and ICs are sealed with resin such as epoxy resin have been widely used in electronic devices.
[0003] In recent years, the amount of heat generated by electronic devices has increased with the miniaturization and density of the devices, and how to dissipate the heat has become an important issue. To address this issue, inorganic fillers with high thermal conductivity have been mixed into the sealing material to increase the thermal conductivity.
[0004] When an inorganic filler is mixed into a sealant, the viscosity of the sealant increases as the amount of the filler increases, and the flowability decreases, which may cause problems such as poor filling. Therefore, a method has been proposed in which a specific phosphorus compound is used as a curing accelerator to increase the flowability of the sealant (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 9-157497 Summary of the Invention [Problem to be solved by the invention]
[0006] With the continuing progress in miniaturization and high density of electronic component devices, there is a demand for a resin composition that can be used as an encapsulant that has excellent flowability while maintaining a higher level of thermal conductivity. The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a resin composition having excellent flowability, and an electronic component device including an element encapsulated with the same. [Means for solving the problem]
[0007] Means for solving the above problems include the following embodiments. <1> A resin composition comprising a resin and an inorganic filler, the inorganic filler containing inorganic particles having an average particle size of 0.07 μm to 0.5 μm. <2> The specific surface area of the inorganic particles is 15 m 2 / g or less, <1> The resin composition according to claim 1. <3> The proportion of the inorganic particles is 3% by mass to 10% by mass of the total inorganic filler. <1> or <2> The resin composition according to claim 1. <4> The inorganic particles are alumina particles. <1> ~ <3> The resin composition according to any one of claims 1 to 10. <5> The proportion of the inorganic particles is 3% by mass to 10% by mass of the total inorganic filler. <1> ~ <4> The resin composition according to any one of claims 1 to 10. <6> the inorganic filler contains the inorganic particles and inorganic particles other than the inorganic particles, and a ratio (A / B) of a specific gravity A of the inorganic particles to a specific gravity B of the inorganic particles other than the inorganic particles is 0.8 to 1.2; <1> ~ <5> The resin composition according to any one of claims 1 to 10. <7> The inorganic filler includes the inorganic particles and inorganic particles other than the inorganic particles, and the inorganic particles other than the inorganic particles include inorganic particles of the same material as the inorganic particles. <1> ~ <6> The resin composition according to any one of claims 1 to 10. <8> For use as an encapsulant for electronic device, <1> ~ <7> The resin composition according to any one of claims 1 to 10. <9> An element and a device for sealing the element <1> ~ <7> and a cured product of the resin composition according to any one of claims 1 to 5. <10> A resin composition comprising a resin and an inorganic filler, the inorganic filler comprising inorganic particles A having a volume average particle diameter of 0.07 μm to 0.5 μm and inorganic particles B other than the inorganic particles A, and a ratio (A / B) of a refractive index A of a substance constituting the inorganic particles A to a refractive index B of a substance constituting the inorganic particles B is 0.9 to 1.5. Effect of the Invention
[0008] According to the present invention, there are provided a resin composition having excellent flowability, and an electronic component device including an element encapsulated with the resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, the embodiment for carrying out the present invention will be described in detail. However, the present invention is not limited to the following embodiment. In the following embodiment, the components (including element steps, etc.) are not essential unless specifically stated. The same applies to the numerical values and their ranges, and they do not limit the present invention. In the present disclosure, the term "step" includes not only a step that is independent of other steps, but also a step that cannot be clearly distinguished from other steps as long as the purpose of the step is achieved. In the present disclosure, a numerical range indicated using "~" includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In the present disclosure, the content or amount of each component in a composition means, when multiple substances corresponding to each component are present in the composition, the total content or amount of the multiple substances present in the composition, unless otherwise specified. In the present disclosure, the particle size of each component in a composition means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified, when multiple types of particles corresponding to each component are present in the composition.
[0010] <Resin composition> A resin composition according to one embodiment of the present disclosure includes a resin and an inorganic filler, and the inorganic filler includes inorganic particles having a volume average particle diameter of 0.07 μm to 0.5 μm (hereinafter also referred to as specific inorganic particles).
[0011] The present inventors have found through their investigations that a resin composition in which the inorganic filler contains specific inorganic particles has superior fluidity compared to a resin composition in which the inorganic filler does not contain specific inorganic particles.
[0012] It is not entirely clear why a resin composition containing specific inorganic particles as an inorganic filler has excellent fluidity, but one possible reason is that the specific inorganic particles are present between inorganic fillers (large diameter particles) having larger particle diameters, thereby reducing the frictional resistance between the large diameter particles.
[0013] Furthermore, the inventors' investigations have revealed that the effect of improving fluidity cannot be obtained even if the volume average particle size of the inorganic particles contained in the inorganic filler is smaller than 0.07 μm or larger than 0.5 μm. The reason for this is not entirely clear, but it is thought that inorganic particles with a volume average particle size smaller than 0.07 μm form aggregates between larger particles, and inorganic particles with a volume average particle size larger than 0.5 μm, when present between larger particles, hinder the movement of the larger particles, and therefore do not play a role in reducing the frictional resistance between the larger particles.
[0014] The volume average particle size of the specific inorganic particles is preferably 0.4 μm or less, more preferably 0.3 μm or less, and even more preferably 0.2 μm or less.
[0015] In the present disclosure, the volume average particle diameter of the specific inorganic particles is the particle diameter (D50) at which the cumulative amount from the small diameter side reaches 50% in the volume-based particle size distribution measured by wet dispersion using a laser diffraction particle size distribution measuring device (Malvern Instruments, "Mastersizer 3000").
[0016] The particle size distribution of the specific inorganic particles is not particularly limited, but from the viewpoint of suppressing aggregation of particles, it is preferable that the ratio of fine particles is small. Specifically, for example, when the specific surface area of the entire specific inorganic particles is 15 m 2 / g or less, and 2The specific surface area of the specific inorganic particles is a value measured by the BET method using "Multisorb 16" manufactured by Yuasa Ionics Corporation.
[0017] The ratio of the specific inorganic particles to the entire inorganic filler is not particularly limited. From the viewpoint of obtaining a sufficient effect of improving the flowability by the specific inorganic particles, the ratio of the specific inorganic particles to the entire inorganic filler is preferably 3% by mass to 10% by mass. It is more preferable that the ratio of the specific inorganic particles to the entire inorganic filler is 3% by mass to 10% by mass, and the volume average particle diameter of the entire inorganic filler is 0.2 μm to 20 μm. Details of the inorganic filler will be described later.
[0018] The shape of the specific inorganic particles is not particularly limited. From the viewpoint of obtaining a sufficient effect of improving the flowability by the specific inorganic particles, the closer to a sphere, the more preferable. Specifically, for example, it is preferable that the circularity of the specific inorganic particles observed by an electron microscope is 0.70 or more. The circularity is expressed by 4π×S / (perimeter) 2 where S is the area of the particle being measured, and circumferential length is the circumferential length of the particle being measured. Circularity can be determined by analyzing electron microscope images using image processing software.
[0019] The material of the specific inorganic particles is not particularly limited. For example, inorganic substances such as silica, alumina, calcium carbonate, zirconium silicate, calcium silicate, silicon nitride, aluminum nitride, boron nitride, beryllia, zirconia, zircon, fosterite, steatite, spinel, mullite, titania, talc, clay, and mica can be mentioned. The specific inorganic particles may be inorganic substances having a flame retardant effect. Examples of inorganic substances having a flame retardant effect include aluminum hydroxide, magnesium hydroxide, composite metal hydroxide such as composite hydroxide of magnesium and zinc, and zinc borate. The material of the specific inorganic particles may be one type or a combination of two or more types. The specific inorganic particles are preferably alumina particles (specific alumina particles).
[0020] The material of the specific inorganic particles may be at least one selected from substances having a refractive index within the range of 1.0 to 2.0. The refractive index in this disclosure is a value specific to a substance (absolute refractive index) when a vacuum is set to 1, and is a value for light with a wavelength of 589.3 nm.
[0021] (resin) The resin contained in the resin composition may be thermosetting or thermoplastic, or may be photocurable. From the viewpoint of reliability, a curable resin is preferable. The curable resin may be one that cures by self-polymerization or one that cures by reaction with a curing agent, a crosslinking agent, or the like.
[0022] When the resin is a curable resin, the functional group that causes the reaction is not particularly limited, and examples thereof include cyclic ether groups such as an epoxy group and an oxetanyl group, a hydroxyl group, a carboxy group, an amino group, an acryloyl group, an isocyanate group, etc. From the viewpoint of the balance of properties as a sealing material, a curable resin containing a cyclic ether group is preferable, and a curable resin containing an epoxy group (epoxy resin) is more preferable.
[0023] When the curable resin is an epoxy resin, the type of the epoxy resin is not particularly limited as long as it has an epoxy group in the molecule. Specific examples of epoxy resins include novolac-type epoxy resins (phenol novolac-type epoxy resins, orthocresol novolac-type epoxy resins, etc.) obtained by epoxidizing novolac resins obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of phenolic compounds such as phenol, cresol, xylenol, resorcin, catechol, bisphenol A, bisphenol F, etc., and naphthol compounds such as α-naphthol, β-naphthol, dihydroxynaphthalene, etc., with an aliphatic aldehyde compound such as formaldehyde, acetaldehyde, propionaldehyde, etc., under an acidic catalyst; triphenylmethane-type epoxy resins obtained by epoxidizing triphenylmethane-type phenolic resins obtained by condensing or co-condensing the above-mentioned phenolic compound with an aromatic aldehyde compound such as benzaldehyde, salicylaldehyde, etc., under an acidic catalyst; and novolac resins obtained by co-condensing the above-mentioned phenolic compound and naphthol compound with an aldehyde compound under an acidic catalyst. diphenylmethane type epoxy resins which are diglycidyl ethers of bisphenol A, bisphenol F, etc.; biphenyl type epoxy resins which are diglycidyl ethers of alkyl-substituted or unsubstituted biphenols; stilbene type epoxy resins which are diglycidyl ethers of stilbene-based phenolic compounds; sulfur-containing epoxy resins which are diglycidyl ethers of bisphenol S, etc.; epoxy resins which are glycidyl ethers of alcohols such as butanediol, polyethylene glycol, and polypropylene glycol; glycidyl ester type epoxy resins which are glycidyl esters of polyvalent carboxylic acid compounds such as phthalic acid, isophthalic acid, and tetrahydrophthalic acid; glycidylamine type epoxy resins in which active hydrogen bonded to nitrogen atoms of aniline, diaminodiphenylmethane, isocyanuric acid, etc. is substituted with a glycidyl group; dicyclopentadiene type epoxy resins which are epoxidized co-condensation resins of dicyclopentadiene and phenolic compounds;Alicyclic epoxy resins such as vinylcyclohexene diepoxide, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, and 2-(3,4-epoxy)cyclohexyl-5,5-spiro(3,4-epoxy)cyclohexane-m-dioxane, which are epoxy-modified epoxy resins in which the olefin bonds in the molecule have been epoxidized; paraxylylene-modified epoxy resins, which are glycidyl ethers of paraxylylene-modified phenolic resins; metaxylylene-modified epoxy resins, which are glycidyl ethers of metaxylylene-modified phenolic resins; terpene-modified epoxy resins, which are glycidyl ethers of terpene-modified phenolic resins; and dicyclopentadiene-modified phenolic resins, which are glycidyl ethers of dicyclopentadiene-modified phenolic resins. Examples of the epoxy resin include pentadiene-modified epoxy resins; cyclopentadiene-modified epoxy resins which are glycidyl ethers of cyclopentadiene-modified phenolic resins; polycyclic aromatic ring-modified epoxy resins which are glycidyl ethers of polycyclic aromatic ring-modified phenolic resins; naphthalene-type epoxy resins which are glycidyl ethers of naphthalene ring-containing phenolic resins; halogenated phenol novolac-type epoxy resins; hydroquinone-type epoxy resins; trimethylolpropane-type epoxy resins; linear aliphatic epoxy resins obtained by oxidizing olefin bonds with peracids such as peracetic acid; aralkyl-type epoxy resins obtained by epoxidizing aralkyl-type phenolic resins such as phenol aralkyl resins and naphthol aralkyl resins; and the like. Furthermore, examples of the epoxy resin include epoxidized silicone resins and epoxidized acrylic resins. These epoxy resins may be used alone or in combination of two or more.;
[0024] The epoxy equivalent (molecular weight / number of epoxy groups) of the epoxy resin is not particularly limited, but from the viewpoint of the balance of various properties such as moldability, reflow resistance, and electrical reliability, it is preferably 100 g / eq to 1000 g / eq, and more preferably 150 g / eq to 500 g / eq.
[0025] The epoxy equivalent of the epoxy resin is a value measured by a method conforming to JIS K 7236:2009.
[0026] The softening point or melting point of the resin is not particularly limited, but is preferably 40°C to 180°C from the viewpoints of moldability and reflow resistance, and more preferably 50°C to 130°C from the viewpoint of handleability during preparation of the resin composition.
[0027] The melting point or softening point of the resin is a value measured by a single cylinder rotational viscometer method described in JIS K 7234:1986 and JIS K 7233:1986.
[0028] The content of the epoxy resin in the curable resin composition is preferably 0.5% by mass to 50% by mass, and more preferably 2% by mass to 30% by mass, from the viewpoints of strength, flowability, heat resistance, moldability, and the like.
[0029] (hardening agent) The resin composition may contain a curing agent. The type of the curing agent is not particularly limited and can be selected depending on the type of resin, the desired properties of the resin composition, and the like. When the resin is an epoxy resin, examples of the curing agent include a phenol curing agent, an amine curing agent, an acid anhydride curing agent, a polymercaptan curing agent, a polyaminoamide curing agent, an isocyanate curing agent, a blocked isocyanate curing agent, etc. From the viewpoint of improving heat resistance, the curing agent is preferably one having a phenolic hydroxyl group in the molecule (phenol curing agent).
[0030] Specific examples of the phenolic hardener include polyhydric phenolic compounds such as resorcin, catechol, bisphenol A, bisphenol F, and substituted or unsubstituted biphenol; novolak-type phenolic resins obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of phenolic compounds such as phenol, cresol, xylenol, resorcin, catechol, bisphenol A, bisphenol F, phenylphenol, and aminophenol, and naphthol compounds such as α-naphthol, β-naphthol, and dihydroxynaphthalene, with an aldehyde compound such as formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, and salicylaldehyde, under an acid catalyst; and polyphenolic compounds such as dimethoxyparaxylene, bis(methoxymethyl)biphenol, and the like. Examples of the phenol curing agent include aralkyl-type phenolic resins such as phenol aralkyl resins and naphthol aralkyl resins synthesized from phenyl and the like; paraxylylene and / or metaxylylene modified phenolic resins; melamine modified phenolic resins; terpene modified phenolic resins; dicyclopentadiene-type phenolic resins and dicyclopentadiene-type naphthol resins synthesized by copolymerization of the above phenolic compounds and dicyclopentadiene; cyclopentadiene modified phenolic resins; polycyclic aromatic ring modified phenolic resins; biphenyl type phenolic resins; triphenylmethane type phenolic resins obtained by condensing or co-condensing the above phenolic compounds with aromatic aldehyde compounds such as benzaldehyde and salicylaldehyde under an acid catalyst; and phenolic resins obtained by copolymerizing two or more of these. These phenolic curing agents may be used alone or in combination of two or more.
[0031] The functional group equivalent of the curing agent (hydroxyl group equivalent in the case of a phenolic curing agent) is not particularly limited. From the viewpoint of the balance of various properties such as moldability, reflow resistance, and electrical reliability, it is preferably 70 g / eq to 1000 g / eq, and more preferably 80 g / eq to 500 g / eq.
[0032] The functional group equivalent of the curing agent (hydroxyl group equivalent in the case of a phenolic curing agent) is a value measured by a method in accordance with JIS K 0070:1992.
[0033] The softening point or melting point of the curing agent is not particularly limited, but is preferably 40° C. to 180° C. from the viewpoints of moldability and reflow resistance, and more preferably 50° C. to 130° C. from the viewpoint of handleability during production of the curable resin composition.
[0034] The melting point or softening point of the curing agent is a value measured by a single cylinder rotational viscometer method described in JIS K 7234:1986 and JIS K 7233:1986.
[0035] The equivalent ratio of the curable resin to the curing agent, that is, the ratio of the number of functional groups in the curing agent to the number of functional groups in the curable resin (number of functional groups in the curing agent / number of functional groups in the curing resin) is not particularly limited. In terms of keeping the amount of unreacted components low, it is preferably set in the range of 0.5 to 2.0, and more preferably set in the range of 0.6 to 1.3. In terms of moldability and reflow resistance, it is even more preferably set in the range of 0.8 to 1.2.
[0036] (Cure accelerator) The resin composition may contain a curing accelerator. The type of the curing accelerator is not particularly limited and can be selected depending on the type of resin, the desired properties of the resin composition, and the like. Examples of the curing accelerator include diazabicycloalkenes such as 1,5-diazabicyclo[4.3.0]nonene-5 (DBN) and 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), cyclic amidine compounds such as 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, and 2-heptadecylimidazole; derivatives of the cyclic amidine compounds; phenol novolac salts of the cyclic amidine compounds or their derivatives; and combinations of these compounds with maleic anhydride, 1,4-benzoquinone, 2,5-toluquinone, 1,4-naphthoquinone, and the like. quinone compounds such as quinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, and phenyl-1,4-benzoquinone; compounds with intramolecular polarization formed by adding compounds with π bonds such as diazophenylmethane; cyclic amidines such as tetraphenylborate salt of DBU, tetraphenylborate salt of DBN, tetraphenylborate salt of 2-ethyl-4-methylimidazole, and tetraphenylborate salt of N-methylmorpholine; ammonium compounds; tertiary amine compounds such as pyridine, triethylamine, triethylenediamine, benzyldimethylamine, triethanolamine, dimethylaminoethanol, and tris(dimethylaminomethyl)phenol; derivatives of the above tertiary amine compounds; ammonium salt compounds such as tetra-n-butylammonium acetate, tetra-n-butylammonium phosphate, tetraethylammonium acetate, tetra-n-hexylammonium benzoate, and tetrapropylammonium hydroxide; tertiary phosphines such as triphenylphosphine, diphenyl(p-tolyl)phosphine, tris(alkylphenyl)phosphine, tris(alkoxyphenyl)phosphine, tris(alkylalkoxyphenyl)phosphine, tris(dialkylphenyl)phosphine, tris(trialkylphenyl)phosphine, tris(tetraalkylphenyl)phosphine, tris(dialkoxyphenyl)phosphine, tris(trialkoxyphenyl)phosphine, tris(tetraalkoxyphenyl)phosphine, trialkylphosphine, dialkylarylphosphine, and alkyldiarylphosphine;Phosphine compounds such as complexes of the tertiary phosphines and organic borons; compounds having intramolecular polarization obtained by adding the tertiary phosphines or the phosphine compounds to maleic anhydride, quinone compounds such as 1,4-benzoquinone, 2,5-toluquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, and phenyl-1,4-benzoquinone, and compounds having a π bond such as diazophenylmethane; compounds having intramolecular polarization obtained by adding the tertiary phosphines or the phosphine compounds to 4-bromophenol, 3-bromophenol, 2-bromophenol, 4-chlorophenol, 3-chlorophenol, 2-chlorophenol, 4-iodophenol, and 3-iodophenol; Compounds having intramolecular polarization obtained by reacting halogenated phenol compounds such as phenol, 2-iodophenol, 4-bromo-2-methylphenol, 4-bromo-3-methylphenol, 4-bromo-2,6-dimethylphenol, 4-bromo-3,5-dimethylphenol, 4-bromo-2,6-di-tert-butylphenol, 4-chloro-1-naphthol, 1-bromo-2-naphthol, 6-bromo-2-naphthol, and 4-bromo-4'-hydroxybiphenyl, followed by a dehydrohalogenation step; tetra-substituted phosphonium compounds such as tetraphenylphosphonium, tetra-substituted phosphonium compounds and tetra-substituted borates having no phenyl group bonded to the boron atom such as tetra-p-tolylborate, and salts of tetraphenylphosphonium compounds with phenol compounds;
[0037] When the resin composition contains a curing accelerator, the amount is preferably 0.1 to 30 parts by mass, more preferably 1 to 15 parts by mass, per 100 parts by mass of the resin component (total of the resin and the curing agent if necessary). When the amount of the curing accelerator is 0.1 parts by mass or more per 100 parts by mass of the resin component, the composition tends to cure well in a short time. When the amount of the curing accelerator is 30 parts by mass or less per 100 parts by mass of the resin component, the curing speed is not too fast and a good molded product tends to be obtained.
[0038] (Inorganic filler) The inorganic filler contained in the resin composition is not particularly limited as long as it contains specific inorganic particles.
[0039] Specific examples of the inorganic filler include inorganic materials such as fused silica, crystalline silica, glass, alumina, calcium carbonate, zirconium silicate, calcium silicate, silicon nitride, aluminum nitride, boron nitride, beryllia, zirconia, zircon, fosterite, steatite, spinel, mullite, titania, talc, clay, and mica. Inorganic fillers having a flame retardant effect may be used. Examples of inorganic fillers having a flame retardant effect include aluminum hydroxide, magnesium hydroxide, composite metal hydroxides such as composite hydroxides of magnesium and zinc, and zinc borate.
[0040] Among the inorganic fillers, silica such as fused silica is preferred from the viewpoint of reducing the linear expansion coefficient, and alumina is preferred from the viewpoint of high thermal conductivity. The inorganic fillers may be used alone or in combination of two or more kinds.
[0041] When the inorganic filler is particulate, its average particle diameter is not particularly limited. For example, the volume average particle diameter of the entire inorganic filler is preferably 0.2 μm to 20 μm, and more preferably 0.5 μm to 15 μm. When the volume average particle diameter of the inorganic filler is 0.2 μm or more, the increase in viscosity of the resin composition tends to be more suppressed. When the volume average particle diameter is 15 μm or less, the filling ability into narrow gaps tends to be more improved. The volume average particle diameter of the inorganic filler can be measured as the particle diameter (D50) at which the accumulation from the small diameter side becomes 50% in the volume-based particle size distribution measured by a laser scattering diffraction method particle size distribution measuring device.
[0042] The inorganic filler preferably contains the specific inorganic particles and inorganic particles other than the specific inorganic particles, and preferably contains the inorganic particles other than the specific inorganic particles in an amount such that the amount of the specific inorganic particles is 3% by mass to 10% by mass of the entire inorganic filler.
[0043] When the inorganic filler contains the specific inorganic particles and inorganic particles other than the specific inorganic particles, it is preferable that the inorganic filler other than the specific inorganic particles contains inorganic particles of the same material as the specific inorganic particles. For example, when the specific inorganic particles are alumina particles, it is preferable that the inorganic filler other than the specific inorganic particles contains alumina particles.
[0044] The average particle diameter of the inorganic particles other than the specific inorganic particles is preferably such that the volume average particle diameter of the entire inorganic filler is in the above-mentioned range. For example, the volume average particle diameter is preferably 0.2 μm to 20 μm, and more preferably 0.5 μm to 15 μm.
[0045] From the viewpoint of improving the fluidity of the resin composition, the ratio (A / B) of the specific gravity A of the specific inorganic particles to the specific gravity B of the inorganic particles other than the specific inorganic particles is preferably 0.8 to 1.2, more preferably 0.9 to 1.1, and even more preferably 0.95 to 1.05. When the specific gravity A of the specific inorganic particles and the specific gravity B of the inorganic particles other than the specific inorganic particles satisfy the above conditions, the specific inorganic particles and the other inorganic particles are unlikely to separate in the resin composition, and the specific inorganic particles are likely to enter between the other inorganic particles, which makes it easy to exhibit the effect of improving the fluidity. When the material of either or both of the specific inorganic particles and the other inorganic particles is a combination of two or more types, it is more preferable that each material satisfies the above relationship.
[0046] From the viewpoint of improving the fluidity of the resin composition, the ratio (A / B) of the refractive index A of the substance constituting the specific inorganic particles to the refractive index B of the substance constituting the inorganic particles other than the specific inorganic particles contained in the inorganic filler is preferably 0.9 to 1.5, more preferably 1.0 to 1.4, and even more preferably 1.1 to 1.3. When the refractive index A of the substance constituting the specific inorganic particles and the refractive index B of the substance constituting the inorganic particles other than the specific inorganic particles satisfy the above conditions, the specific inorganic particles and the other inorganic particles are difficult to separate in the resin composition, and the specific inorganic particles are likely to enter between the other inorganic particles, so that the effect of improving the fluidity is easily exhibited. When the material of either or both of the specific inorganic particles and the other inorganic particles is a combination of two or more types, it is more preferable that each material satisfies the above relationship.
[0047] The content of the inorganic filler in the resin composition is not particularly limited. From the viewpoint of fluidity and strength, it is preferably 30% by volume to 90% by volume of the entire resin composition, more preferably 35% by volume to 80% by volume, and even more preferably 40% by volume to 70% by volume. When the content of the inorganic filler is 30% by volume or more of the entire resin composition, the properties such as the thermal expansion coefficient, thermal conductivity, and elastic modulus of the cured product tend to be further improved. When the content of the inorganic filler is 90% by volume or less of the entire resin composition, the increase in viscosity of the resin composition is suppressed, and the fluidity is further improved, tending to improve moldability.
[0048] [Various additives] In addition to the above-mentioned components, the resin composition may contain various additives such as coupling agents, ion exchangers, release agents, flame retardants, colorants, stress relaxation agents, etc. The resin composition may contain various additives known in the art as necessary, other than the additives exemplified below.
[0049] (Coupling Agent) The resin composition may contain a coupling agent in order to enhance the adhesion between the resin component and the inorganic filler. Examples of the coupling agent include known coupling agents such as silane-based compounds such as epoxy silane, mercapto silane, amino silane, alkyl silane, ureido silane, vinyl silane, titanium-based compounds, aluminum chelate compounds, and aluminum / zirconium-based compounds.
[0050] When the resin composition contains a coupling agent, the amount of the coupling agent is preferably 0.05 parts by mass to 5 parts by mass, more preferably 0.1 parts by mass to 2.5 parts by mass, based on 100 parts by mass of the inorganic filler. When the amount of the coupling agent is 0.05 parts by mass or more based on 100 parts by mass of the inorganic filler, the adhesion to the frame tends to be further improved. When the amount of the coupling agent is 5 parts by mass or less based on 100 parts by mass of the inorganic filler, the moldability of the package tends to be further improved.
[0051] (Ion exchanger) The curable resin composition may contain an ion exchanger. In particular, when the curable resin composition is used as a sealing molding material, it is preferably contained from the viewpoint of improving the moisture resistance and high-temperature storage characteristics of the electronic component device provided with the element to be sealed. The ion exchanger is not particularly limited, and conventionally known ones can be used. Specifically, examples include hydrotalcite compounds and hydrous oxides of at least one element selected from the group consisting of magnesium, aluminum, titanium, zirconium, and bismuth. The ion exchanger may be used alone or in combination of two or more. Among them, hydrotalcite represented by the following general formula (A) is preferable.
[0052] Mg (1-X) Al X (OH)2(CO3) X / 2 ·mH2O ……(A) (0 < X ≦ 0.5, m is a positive number)
[0053] When the resin composition contains an ion exchanger, the content is not particularly limited as long as it is an amount sufficient to capture ions such as halogen ions, etc. For example, the content is preferably 0.1 to 30 parts by mass, and more preferably 1 to 10 parts by mass, per 100 parts by mass of the resin component.
[0054] (Release agent) The resin composition may contain a mold release agent from the viewpoint of obtaining good releasability from the mold during molding. The mold release agent is not particularly limited, and a conventionally known one may be used. Specific examples include carnauba wax, higher fatty acids such as montanic acid and stearic acid, higher fatty acid metal salts, ester waxes such as montanic acid esters, polyolefin waxes such as oxidized polyethylene and non-oxidized polyethylene, etc. The mold release agent may be used alone or in combination of two or more kinds.
[0055] When the resin composition contains a release agent, the amount is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, based on 100 parts by mass of the resin component. When the amount of the release agent is 0.01 parts by mass or more based on 100 parts by mass of the resin component, sufficient releasability tends to be obtained. When the amount is 10 parts by mass or less, better adhesion tends to be obtained.
[0056] (Flame retardant) The resin composition may contain a flame retardant. The flame retardant is not particularly limited, and a conventionally known one may be used. Specific examples include organic or inorganic compounds containing halogen atoms, antimony atoms, nitrogen atoms, or phosphorus atoms, metal hydroxides, etc. The flame retardant may be used alone or in combination of two or more.
[0057] When the resin composition contains a flame retardant, the amount is not particularly limited as long as it is an amount sufficient to obtain the desired flame retardant effect. For example, the amount is preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, per 100 parts by mass of the resin component.
[0058] (Coloring agent) The resin composition may further contain a colorant. Examples of the colorant include known colorants such as carbon black, organic dyes, organic pigments, titanium oxide, red lead, and red iron oxide. The content of the colorant can be appropriately selected depending on the purpose. The colorant may be used alone or in combination of two or more.
[0059] (Stress reliever) The resin composition may contain a stress relaxation agent such as silicone oil and silicone rubber particles. By containing a stress relaxation agent, it is possible to further reduce the warpage deformation of the package and the occurrence of package cracks. Examples of the stress relaxation agent include known stress relaxation agents (flexible agents) that are generally used. Specifically, examples include thermoplastic elastomers such as silicone-based, styrene-based, olefin-based, urethane-based, polyester-based, polyether-based, polyamide-based, and polybutadiene-based elastomers, rubber particles such as NR (natural rubber), NBR (acrylonitrile-butadiene rubber), acrylic rubber, urethane rubber, and silicone powder, and rubber particles having a core-shell structure such as methyl methacrylate-styrene-butadiene copolymer (MBS), methyl methacrylate-silicone copolymer, and methyl methacrylate-butyl acrylate copolymer. The stress relaxation agent may be used alone or in combination of two or more types.
[0060] (Method for preparing resin composition) The method for preparing the resin composition is not particularly limited. A general method includes a method in which a predetermined amount of components is thoroughly mixed with a mixer or the like, then melt-kneaded with a mixing roll, an extruder, or the like, cooled, and pulverized. More specifically, for example, a method in which a predetermined amount of the above-mentioned components is uniformly stirred and mixed, kneaded with a kneader, roll, extruder, or the like that has been heated to 70°C to 140°C in advance, cooled, and pulverized can be mentioned.
[0061] The resin composition is preferably solid at room temperature and normal pressure (for example, 25°C, atmospheric pressure). When the resin composition is solid, the shape is not particularly limited, and examples thereof include powder, granules, tablets, etc. When the resin composition is in tablet form, the dimensions and mass are preferably set to be suitable for the molding conditions of the package from the viewpoint of handling.
[0062] <Electronic component equipment> An electronic component device according to one embodiment of the present disclosure includes an element and a cured product of the above-described resin composition that encapsulates the element. Examples of electronic component devices include devices obtained by mounting elements (active elements such as semiconductor chips, transistors, diodes, and thyristors, and passive elements such as capacitors, resistors, and coils) on a support member such as a lead frame, a pre-wired tape carrier, a wiring board, glass, a silicon wafer, or an organic substrate, and then sealing the resulting element portion with a resin composition. More specifically, typical resin-sealed ICs such as DIP (Dual Inline Package), PLCC (Plastic Leaded Chip Carrier), QFP (Quad Flat Package), SOP (Small Outline Package), SOJ (Small Outline J-lead package), TSOP (Thin Small Outline Package), and TQFP (Thin Quad Flat Package) have a structure in which an element is fixed on a lead frame, and terminal portions of the element such as bonding pads and lead portions are connected by wire bonding, bumps, or the like, and then sealed by transfer molding or the like using a resin composition; TCP (Tape Carrier Package) has a structure in which an element connected to a tape carrier by bumps is sealed with a resin composition; and COB (Chip On Board) has a structure in which an element is connected to wiring formed on a support member by wire bonding, flip chip bonding, solder, or the like, and sealed with a resin composition. Examples of such a package include a BGA (Ball Grid Array), CSP (Chip Size Package), MCP (Multi Chip Package), etc., which have a structure in which an element is mounted on the surface of a support member having terminals for connecting a wiring board formed on the back side thereof, the element is connected to wiring formed on the support member by bump or wire bonding, and then the element is sealed with a resin composition. The resin composition can also be suitably used in printed wiring boards.
[0063] Methods for encapsulating electronic device components using a resin composition include low-pressure transfer molding, injection molding, compression molding, etc. Of these, low-pressure transfer molding is the most common. EXAMPLES
[0064] The above embodiment will be specifically described below using examples, but the scope of the above embodiment is not limited to these examples.
[0065] (Preparation of Resin Composition) The components shown below were mixed in the blending ratios (parts by mass) shown in Table 1 to prepare resin compositions of Examples and Comparative Examples.
[0066] Epoxy resin 1: Bisphenol type epoxy resin, Nippon Steel & Sumitomo Metal Corporation, product name "YSLV-80XY") Epoxy resin 2: Multifunctional epoxy resin, Mitsubishi Chemical Corporation, product name "1032H60") Epoxy resin 3: Biphenyl type epoxy resin, Mitsubishi Chemical Corporation, product name "YX-4000") Hardener 1: Multifunctional phenolic resin, Air Water Inc., product name "HE910") · Curing accelerator 1…Phosphorus-based curing accelerator
[0067] Inorganic filler A1: Alumina particles with a volume average particle size of 9.0 μm Inorganic filler A2: Alumina particles with a volume average particle size of 0.1 μm and a specific surface area of 5.1 m 2 / g Inorganic filler S1: Silica particles with a volume average particle size of 2.6 μm Inorganic filler S2: Silica particles with a volume average particle size of 0.03 μm Inorganic filler S3: Silica particles with a volume average particle size of 0.8 μm
[0068] (Liquidity assessment) The flowability of the resin composition was evaluated by a spiral flow test. Specifically, the resin composition was molded using a spiral flow measurement die conforming to EMMI-1-66, and the flow distance (cm) of the molded resin composition was measured. The resin composition was molded using a transfer molding machine under the conditions of a die temperature of 180°C, molding pressure of 6.9 MPa, and curing time of 120 seconds. The results are shown in Table 1.
[0069] [Table 1]
[0070] As shown in Table 1, the resin compositions of Examples 1 to 3, in which the inorganic filler contained specific inorganic particles (inorganic filler A2), were evaluated as having higher fluidity than the resin composition of Comparative Example 1, in which the inorganic filler did not contain specific inorganic particles. Similar results were obtained even when the composition of the epoxy resin or the composition of the inorganic filler was changed. The resin composition of Comparative Example 2 in which the inorganic filler contained silica particles having a volume average particle diameter of 0.03 μm and the resin composition of Comparative Example 3 in which the inorganic filler contained silica particles having a volume average particle diameter of 0.8 μm both had lower fluidity ratings than the resin compositions of the Examples.
[0071] The disclosures of Japanese Patent Applications Nos. 2016-253846 and 2016-253847 are incorporated herein by reference in their entireties. All publications, patent applications, and technical standards mentioned in this specification are incorporated by reference into this specification to the same extent as if each individual publication, patent application, and technical standard was specifically and individually indicated to be incorporated by reference.
Claims
1. A composition comprising a curable resin and an inorganic filler, the inorganic filler comprising inorganic particles A having an average particle diameter of 0.07 μm to 0.3 μm and inorganic particles B other than the inorganic particles A; The specific surface area of the inorganic particles A is 15 m 2 / g or less, The volume average particle diameter of the inorganic particles B is 0.5 μm to 15 μm. Resin composition.
2. The resin composition described in claim 1, wherein the curable resin is an epoxy resin.
3. A resin composition as described in claim 2, wherein the content of the epoxy resin in the resin composition is 0.5 mass% to 50 mass%.
4. A resin composition described in any one of claims 1 to 3, wherein the content of the inorganic filler is 30 volume % to 90 volume % of the total resin composition.
5. A resin composition described in any one of claims 1 to 4, wherein the proportion of inorganic particles A is 3% by mass to 10% by mass of the total inorganic filler.
6. A resin composition described in any one of claims 1 to 5 for use as a sealing material for electronic component devices.
7. An electronic component device comprising an element and a cured product of the resin composition described in any one of claims 1 to 6 that encapsulates the element.